2019
DOI: 10.1002/rcm.8513
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of unknown impurities of paromomycin in a 15% topical cream by liquid chromatography combined with mass spectrometry

Abstract: Rationale Characterization of unknown impurities in degraded paromomycin 15% topical cream samples by ultra‐high‐performance liquid chromatography/tandem mass spectrometry (UHPLC/MS/MS) gas‐phase fragmentation is described. Methods A volatile reversed‐phase high‐performance liquid chromatography/charged aerosol detection (RP‐HPLC/CAD) method was developed and validated for fast and consistent analysis of the paromomycin potency and impurity values in drug substance and drug product samples. A Veo charged aeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Zhu et al 70 used LC-MS to study the fragmentation patterns of impurities in sodium drug substance and eye drops, deduced the chemical structures of impurities, confirmed the structure with 1D and 2D NMR data, and achieved the structures characterization of 2 unknown impurities and 6 unknown degradation products and a plausible mechanism for the formation of the degradation products was also proposed. Hertzler et al 71 study fragmentation patterns and fragmentation pathways of paromomycin impurities based on UHPLC/MS/MS and the literature of other structurally related aminoglycoside compounds, and made reasonable suggestions for the storage methods of drugs.…”
Section: Mass Spectroscopymentioning
confidence: 99%
“…Zhu et al 70 used LC-MS to study the fragmentation patterns of impurities in sodium drug substance and eye drops, deduced the chemical structures of impurities, confirmed the structure with 1D and 2D NMR data, and achieved the structures characterization of 2 unknown impurities and 6 unknown degradation products and a plausible mechanism for the formation of the degradation products was also proposed. Hertzler et al 71 study fragmentation patterns and fragmentation pathways of paromomycin impurities based on UHPLC/MS/MS and the literature of other structurally related aminoglycoside compounds, and made reasonable suggestions for the storage methods of drugs.…”
Section: Mass Spectroscopymentioning
confidence: 99%
“…Hertzler et al. [27] developed and validated a volatile reversed‐phase HPLC‐CAD method that identified nine PRM impurities. Modifications such as acetylation, carbamylation, addition of hexose and loss of glucosamine were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Given that PRM and its impurities have similar structures without UV-absorbing chromophores, decent detection techniques should be applied, and few LC-based methods for detecting PRM in human biological matrices have been reported [23][24][25][26]. Hertzler et al [27] developed and validated a volatile reversed-phase HPLC-CAD method that identified nine PRM impurities. Modifications such as acetylation, carbamylation, addition of hexose and loss of glucosamine were observed.…”
Section: Introductionmentioning
confidence: 99%